Exploring cultural geography field course using story maps. Issue 2 (3rd April 2019) - Mukherjee, Falguni
ABSTRACT: This article explores the use of Story Maps in a cultural geography field course that uses a place-based approach to understand the Delta Blue's culture. In this study, Story Maps was used to capture and map student experiences as they engaged in a field study. Student experiences are captured by incorporating different data mediums such as narratives, personal reflections, digital photos, videos and website. Such a project has the potential to challenge students to work collectively and present a coherent story of their field experiences. This, in turn, can be used to improve the design and experience of a field course. The study demonstrates that the availability of simple web-based mapping platform such as Story maps provides students the ability to harness technology to create geocoded narratives, visual representations and spatial documentation to map their field course experience.